2006
DOI: 10.1111/j.1399-0012.2006.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

De novo gastrointestinal tumours after renal transplantation: Role of CMV and EBV viruses

Abstract: The development of new and more effective immunosuppressive agents has provided long-term survival for transplant recipients, thereby increasing the risk of de novo malignancy in chronic immunocompromised hosts. While de novo post-transplant lymphoproliferative diseases and skin cancer has been shown to have an increased incidence in long-term surviving solid organ transplant recipients, the association with gastrointestinal (GI) cancer is controversial. Over 12 yr, 20 patients (5%) out of 395 renal transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Reactivation of CMV and the Epstein-Barr virus (EBV) is an established risk factor in developing malignancies after transplantation, but only EBV, as the etiologic agent of posttransplantation lymphoproliferative disorder, has been directly associated with malignancies [ 46 ]. A recent case series by Adani et al [ 47 ] reported four patients who developed gastrointestinal tumors following transplantation; all had CMV and EBV reactivation within 3 months after the procedure.…”
Section: And Gastrointestinal Tumorsmentioning
confidence: 98%
“…Reactivation of CMV and the Epstein-Barr virus (EBV) is an established risk factor in developing malignancies after transplantation, but only EBV, as the etiologic agent of posttransplantation lymphoproliferative disorder, has been directly associated with malignancies [ 46 ]. A recent case series by Adani et al [ 47 ] reported four patients who developed gastrointestinal tumors following transplantation; all had CMV and EBV reactivation within 3 months after the procedure.…”
Section: And Gastrointestinal Tumorsmentioning
confidence: 98%
“…For example the analysis of DNA damage could be associated with HPV isolation at the time of pap test screening, or with EBV viral load determination in the follow-up of transplant patients [28] . Retrospective and prospective studies could be implemented, analyzing possible correlation between frequency of different virus reactivations, severity of these reactivations, evidence of genetic damage in cells that harbor latent viruses and development of malignancies, in order to better define the importance of evocative findings [56] : ideal candidates for these studies would be populations of immunocompromised patients such as those in post-transplant settings [57] . Chronic infections, clinically manifest or subclinical, are an additional interesting condition for virus related DNA damage investigation [37] .…”
Section: Testing the Hypothesismentioning
confidence: 99%